PENANGANAN ANAK YANG BERHADAPAN DENGAN HUKUM BERDASARKAN UNDANG UNDANG NOMOR 11 TAHUN 2012 TENTANG SISTEM PERADILAN PIDANA ANAK - Andri Purba Yuana (Journal of Law ( Jurnal Ilmu Hukum ), 2019)
ABSTRACTThe problem with street children is not a new problem. These problems tend to appear in big cities including Samarinda in them. The problems which are classified into social problems arise from social changes in society. This factor of social change includes global change that is very fast including science and technology. Urban communities which are generally preoccupied with individual problems make it even more indifferent to the surrounding environment. The impact is the depletion of social relations and a sense of concern for the community and its environment, one of which is street children around them.The method used in this study is a normative juridical method, data or information obtained through library research. From the results of the literature research, secondary data were obtained which included primary legal materials, secondary legal materials and tertiary legal materials. The problem that the author discussed in this paper is the legal psychology perspective on the problem of street children who are faced with the law and the causes of street children facing the law.Based on the results of the study, it can be concluded Based on the data that I have obtained, in general it shows that there are peers' invitations and the economic needs of their families which must be fulfilled as a strong reason for street children to dare to face the law. Besides that, the perspective of legal psychology considers that the age of street children is very influential on psychic street children who commit criminal acts or children in conflict with the law, because the needs of children to grow and develop naturally are not fulfilled due to bad behavior in the streets of teenage street children. (15-21 years) imitated by street children who are categorized as children (7-14 years) and some of the factors that cause street children to face the law include: Parents encourage children to work with reasons to help the family economy; Cases of violence and mistreatment of children by parents are increasing so that children run to the streets; Children are threatened with dropping out of school because parents cannot afford to pay school fees; More and more children are living on the streets because the cost of expensive / increased house contracts; The emergence of competition with adult workers on the streets, so that children are depressed doing work at high risk of safety and exploitation of children by adults on the streets; Children become longer on the streets so new problems arise; and street children are victims of extortion, and sexual exploitation of female street children. Keywords: Street Children, Crime, Psychology